STRATEGI KEMITRAAN SEBAGAI UPAYA PEMBERDAYAAN EKONOMI DALAM MENINGKATKAN PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS PADA USAHA KOPERASI TERNAK TANI SYARI’AH MITRA SUBUR KABUPATEN BONDOWOSO) - Nurjannah, Feby (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
Partnership is a business cooperation which is a business strategy carried out between two or more parties with the principles of mutual need, mutual enlargement and mutual benefit. This can be seen because basically each party must have weaknesses and advantages, precisely with the weaknesses and advantages of each party will complement each other in the sense that one party will fill in by fostering the weaknesses of the other and vice versa. KTTS is a cooperative legal entity that aims to empower the Bondowoso community. The research focused on: 1) How is the business partnership strategy of Mitra Subur Shari'ah Farmer Livestock Cooperative as an effort to empower the community's economy? 2) What is the impact of the partnership strategy of the Mitra Subur Syari'ah Farmer Livestock Cooperative on increasing the income of the Bondowoso Regency community? 3) What is the impact of the partnership strategy of the Mitra Subur Syari'ah Farmer Livestock Cooperative on the economic welfare of the Bondowoso Regency community? 4) What are the supporting and inhibiting factors of the partnership strategy of the Mitra Subur Syari'ah Farmer Livestock Cooperative? This type of research is descriptive qualitative research with the key instrument of the researcher himself. The research location is the Sharia Tani Livestock Cooperative in Karanganyar Village, Tegal Ampel District, Bondowoso Regency. Data collection used interviews, documentation, and observation methods. Data analysis was carried out using data reduction techniques, data presentation, and conclusion drawing. The data sources obtained consisted of primary and secondary data sources. The results of this study indicate that the partnership pattern run by KTTS is a core plasma partnership pattern with the institution as a provider of goods and product marketing. The existence of the Sharia Tani Livestock Cooperative partnership concept can provide empowerment, increased income, and welfare for its members/partners. Empowerment is carried out in the form of guidance to members on how to be able to raise livestock in a more effective and efficient way and time. The impact will certainly greatly affect the increase in income and welfare of each member.